Microphase-Tuned Segmented Polyurethane Porous Architecture for Selective Atmospheric Polycyclic Aromatic Hydrocarbons Capture - Hamm-Hahn, L (American Chemical Society, 2025)
Passive air monitoring requires polymer sorbents that combine selective interfacial interactions with fast capture of pollutants. We design porous polyurethane (PU) with tunable aromatic hard-segment (HS) content (MDI:BDO:PCL = 6:5:1, 4.5:5:1, 3:5:1, namely PU-1/PU-2/PU-3) and benchmark them against a commercial foam (C-PU). In these materials, HS domains act as physically cross-linked reinforcements embedded in a soft PCL matrix, or soft-segments (SS), so that the HS fraction/aromaticity governs microphase separation and crystallinity, tunes modulus, and elevates the dispersion component of the surface free energy (SFE). Multiscale characterization establishes a clear structure-property link. PU-2 provides the best balance of mechanical integrity, dispersive SFE = 46.33 +/- 0.21 mN m(-1), and a controlled pore architecture (similar to 150-300 mu m). In performance reference compound (PRC) calibrated deployments, PU-2 achieves 89.3 +/- 6.7% recovery, which is more than twice that of the commercial foam (41.2 +/- 6.6%). Field tests confirm superior uptake of low-molecular-weight polycyclic aromatic hydrocarbons, PAHs, (MW < 202 g mol(-1)), enabling urban-rural discrimination in 17 days (versus similar to 90 days for commercial foams). These results define a structure-property-performance pathway in which HS aromaticity governs microphase/thermal metrics and SFE, which together control selective uptake, thereby positioning hard-segment tuning as a practical polymer design lever for applied PU sorbents compatible with passive air monitoring requirements.